2017
DOI: 10.1155/2017/8231358
|View full text |Cite
|
Sign up to set email alerts
|

Antihepatocarcinoma Effect of Portulaca oleracea L. in Mice by PI3K/Akt/mTOR and Nrf2/HO‐1/NF‐κB Pathway

Abstract: The purpose of the present study was to evaluate the pharmacological effects of Portulaca oleracea L. (Purslane) (PL) on N-nitrosodiethylamine- (NDEA-) induced hepatocellular carcinomas (HCC) and explore its potential mechanism. Mice were randomly assigned to four groups: control group, NDEA group, NDEA + Purslane (100 mg/kg) group, and NDEA + Purslane (200 mg/kg) group. The animal of each group was given NDEA (100 ppm) in drinking water. 1 h later, Purslane dissolved in PBS was intragastrically administered f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…These results show that icariin and quercetin may be effective in reversing high glucoseinduced Akt protein phosphorylation, and are in agreement with results of previous studies [9,10]. Inhibition of Akt pathway may have significantly reduced the protective effect of these compounds on neuronal cell apoptosis, an indication that they exerted their effects via the Akt pathway.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results show that icariin and quercetin may be effective in reversing high glucoseinduced Akt protein phosphorylation, and are in agreement with results of previous studies [9,10]. Inhibition of Akt pathway may have significantly reduced the protective effect of these compounds on neuronal cell apoptosis, an indication that they exerted their effects via the Akt pathway.…”
Section: Discussionsupporting
confidence: 92%
“…The serine/threonine-specific protein kinase (Akt) exists at the intersection of many signal pathways, and is involved in cell viability, while inhibiting cell apoptosis [9]. Studies have reported the involvement of bcl-2 and bax in apoptosis [10].…”
Section: Icariinmentioning
confidence: 99%
“…A wide range of pharmacological effects were shown for P. oleracea extracts, including antibacterial [10], hypolipidemic, anti-aging, anti-inflammatory [11,12], skeletal muscle relaxant [11,13], analgesic, wound healing [14], hypoglycemic [15], neuropharmacological [16], bronchodilatory [14,17], hypocholesterolemic [18], and antioxidant activities [15,19,20]. Other studies showed the importance of purslane consumption in the reduction of the occurrence of many diseases such as cancer [21,22] and heart disease [23]. P. oleracea is also consumed as a vegetable, especially in the Mediterranean Basin, where stems and leaves are similar to spinach in its salty and slightly acidic taste.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that PO made a decrement in T lymphocytes proliferation, an increment in Th1/Th2 ratio toward to Th1 and anti-cancer effects (Askari et al, 2016[ 10 ]). Moreover, Guoyin et al (2017[ 27 ]) showed that PO decreased interleukin-6 (IL-6), IL-1β, tumor necrosis factor-α (TNF-α) in N-nitrosodiethylamine (NDEA) induced hepatocellular carcinomas (HCC). Furthermore, PO markedly reduced MDA and raised SOD in serum.…”
Section: Discussionmentioning
confidence: 99%
“…PO markedly diminished NF-κB and inhibitor of NF-κBα (IκBα) expression and enhanced Nrf2 expression. It is concluded that PO possesses anti-oxidant and anti-inflammatory properties in hepatocellular carcinomas (Guoyin et al, 2017[ 27 ]). It has been demonstrated that PO polysaccharides have a strong scavenging activity against superoxide anion, nitric oxide, hydroxyl and 1, 1-diphenyl-2-picrylhydrazyl radicals.…”
Section: Discussionmentioning
confidence: 99%